2021
DOI: 10.1016/j.jiac.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological findings of silent hypoxia among COVID-19 patients

Abstract: The aim of this study was to describe the clinical and radiological findings of COVID-19 patients with “silent hypoxia,” who had no dyspnea on admission even though their oximetry saturation was less than 94%. This retrospective cohort study included all COVID-19 patients (n=270) at a large tertiary care hospital between January 31 and August 31, 2020. Clinical and radiological characteristics of patients who met our criteria of “silent hypoxia”, which included those who reported no dyspnea even tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
1
12
0
2
Order By: Relevance
“…If considered together, the functional estimates (e.g., arterial blood gases, pulse oximetry, etc.) may provide an accurate assessment of the patient's oxygenation status and prevent poor outcomes ( 36 , 37 ). In contrast to this, the structural findings of lung injury may elucidate hidden pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…If considered together, the functional estimates (e.g., arterial blood gases, pulse oximetry, etc.) may provide an accurate assessment of the patient's oxygenation status and prevent poor outcomes ( 36 , 37 ). In contrast to this, the structural findings of lung injury may elucidate hidden pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective cohort study by Okuhama et al . [ 5 ] reported the incidence of silent hypoxia to be 3%, and the authors defined hypoxia to be SpO2<94%. They reported that the patients with silent hypoxia might also have a poor prognosis but not associated with old age or chronic diseases and suggested that some other mechanisms might be involved in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of silent hypoxia in COVID-19 has been reported to be 32%–65% in various studies. [ 4 5 6 ] The reports on patients with silent hypoxia are conflicting, with some studies reporting poorer outcomes while others reporting better outcomes. [ 7 ] In the pandemic setting, patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are advised to isolate at home due to the non-availability of hospital beds and seek hospitalisation when red flags such as breathlessness and tachypnoea occur.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is a global problem. COVID-19 leads to acute and critical pneumonia, although the clinical courses vary [ [1] , [2] , [3] ]. Pulmonary fibrosis secondary to COVID-19 is an essential problem because it might prolong or even deteriorate respiratory symptoms in patients recovering from COVID-19, and pulmonary fibrosis in COVID-19 is thought to be due to an abnormal repair process following lung injury caused by an excessive inflammatory response, abnormality of lung epithelium, mesenchyme, and macrophages, and mechanical injuries in alveoli [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%